Allyship in Residency: An Introductory Module on Medical Allyship for Graduate Medical Trainees - Sarah Martinez; Joseph Araj; Symone Reid; Jeslyn Rodriguez; Mytien Nguyen; Dorcas Boahema Pinto; Pamela Y. Young; Anicia Ivey; Alexis Webber; Hyacinth Mason (Association of American Medical Colleges, 2021)
Introduction Lack of diversity impacts research, medical curricula, and medical trainees' ability to provide equitable patient care. The concept of allyship, defined as a supportive association between identities with power and privilege and marginalized identities, provides an optimal framework for enhancing education about health equity. Currently, there are no established curricula focused on allyship and limited mention within current medical training literature. We propose use of allyship to increase graduate medical trainee understanding of diversity and focus on health equity. Methods We developed a 1-hour workshop aimed at helping residents understand the definition of allyship, effective allyship to patients and colleagues, and allyship differences across communities. The workshop consisted of pre- and postassessment surveys, a didactic presentation module, and facilitated case study discussions. It was conducted locally on four occasions across pediatrics, family medicine, surgery, and emergency medicine residency programs. Results An analysis of the 101 preassessment and 58 postassessment survey responses revealed an increased level of knowledge regarding allyship (p < .001) and increased comprehension of allyship competencies (p < .001). All workshop learning objectives demonstrated positive change postmodule. Discussion With an increasing need for curricula to address health equity in medical trainees, this workshop serves as a unique and effective approach to expanding cultural responsiveness skills under the lens of allyship. Specifically, the workshop functions as a constructive introduction to allyship principles and practices and can serve as a foundation on which residents can build more robust skills as a part of their allyship journey.